Ageing and productivity: Introduction - David E. Bloom; Alfonso Sousa-Poza (Institute for the Study of Labor (IZA), 2013)
Population ageing will be the dominant feature of the world's demographic landscape in the coming decades, raising concerns about labor productivity and about economic outcomes at both the individual, enterprise, and macro levels. The articles in this special issue of Labour Economics define and address key issues with respect to the interplay of ageing, workforce productivity, and economic performance. Taken as a whole, the articles dispel some of the concerns, sharpen our understanding of others, and highlight behavioural changes, business practice adaptations, and public policy reforms that can offset the economic effects of population ageing.
Keywords: J11; J14; J18; 330; ageing; productivity